2011
DOI: 10.1111/j.1469-8749.2011.04091.x
|View full text |Cite
|
Sign up to set email alerts
|

Informing evidence‐based clinical practice guidelines for children with cerebral palsy at risk of osteoporosis: a systematic review

Abstract: Evidence-based clinical practice guidelines were created outlining the suggested role of weight-bearing activities, vitamin D and calcium supplementation, and bisphosphonate use for children with CP with low BMD at risk of fragility fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 36 publications
0
64
0
1
Order By: Relevance
“…For example, although using a standing frame to support hip joint development has some scant evidence, more research is needed for guidance on positioning and duration and frequency of standing (Bush et al, 2010). Furthermore, a systematic review suggests that standing frame recommendations for osteoporosis prevention cannot be supported (Fehlings et al, 2012) due to conflicting findings, small sample sizes, short study durations, and variability in weight bearing in the studies available. Young people report that standing frames are primarily useful for body structure and function.…”
Section: Size-lack Of Spacementioning
confidence: 99%
“…For example, although using a standing frame to support hip joint development has some scant evidence, more research is needed for guidance on positioning and duration and frequency of standing (Bush et al, 2010). Furthermore, a systematic review suggests that standing frame recommendations for osteoporosis prevention cannot be supported (Fehlings et al, 2012) due to conflicting findings, small sample sizes, short study durations, and variability in weight bearing in the studies available. Young people report that standing frames are primarily useful for body structure and function.…”
Section: Size-lack Of Spacementioning
confidence: 99%
“…Despite these, standing frames are part of accepted practice in the UK in children with CP GMFCS IV and V. Professionals have opinions informed by clinical experience; however, there is little research evidence to confirm whether standing frames are beneficial or cause harm. Recent systematic reviews (Bush et al , 2010; Fehlings et al, 2012; Paleg, Smith, and Glickman, 2013) have demonstrated limited and conflicting evidence for their benefit with respect to body structure and function. Although the most recent review (Paleg, Smith, and Glickman, 2013) claimed a positive effect on BMD, hip stability, and range of movement at the hip, knee, and ankle with variable duration of standing frame use, Fehlings et al (2012) found no such evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews (Bush et al , 2010; Fehlings et al, 2012; Paleg, Smith, and Glickman, 2013) have demonstrated limited and conflicting evidence for their benefit with respect to body structure and function. Although the most recent review (Paleg, Smith, and Glickman, 2013) claimed a positive effect on BMD, hip stability, and range of movement at the hip, knee, and ankle with variable duration of standing frame use, Fehlings et al (2012) found no such evidence. A consensus statement acknowledged the limited evidence (Gericke, 2006) but still recommended that standing frames be used from age 12 months in children with CP and GMFCS IV and V (Gericke, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…But a method of treatment for bone fragility has not been established. 3) Bone metabolism markers, as well as osteogenesis and bone resorption markers, tended to decrease markedly at around ages 8 and 15 in seriously disabled children. It is interesting that the decrease around 8 years old would be related to the stage of a fracture.…”
Section: Discussionmentioning
confidence: 97%